Quercetin, quercetin glycosides and taxifolin differ in their ability to induce AhR activation and CYP1A1 expression in HepG2 cells - Vrba, Jiri; Kren, Vladimir; Vacek, Jan; Papouskova, Barbora; Ulrichova, Jitka (Phytotherapy research, 2012)
The natural flavonoid quercetin is a low affinity ligand of the aryl hydrocarbon receptor (AhR), a transcription factor regulating the expression of cytochrome P450 (CYP) 1A enzymes. This study examined the ability of quercetin, isoquercitrin (quercetin-3-O-glucoside), rutin (quercetin-3-O-rutinoside) and taxifolin (dihydroquercetin) to activate AhR and to induce CYP1A1 expression in human hepatoma HepG2 cells. Gene reporter assays showed that quercetin significantly activated AhR and triggered CYP1A1 transcription after 24 h exposure. These effects were, however, much lower than those of 2,3,7,8-tetrachlorodibenzo-p-dioxin, a prototypical AhR ligand. Quercetin also induced a significant increase in CYP1A1 mRNA levels together with a moderate increase in the level of CYP1A1 activity. In contrast, isoquercitrin and rutin had negligible effects on AhR activity and CYP1A1 expression. Taxifolin at the highest concentration tested (50 µm) produced a mild non-significant increase in AhR activity and CYP1A1 transcription. Taxifolin also significantly increased CYP1A1 mRNA expression, but this effect was approximately 15 times weaker than that of quercetin and was not accompanied by induction of CYP1A1 activity. It is concluded that quercetin, but not its 3-O-glycosides isoquercitrin and rutin, induces AhR activation and CYP1A1 expression in HepG2 cells and that the CYP1A1-inducing activity of taxifolin has a low toxicological potential.
Keywords: Rutin; Hep G2 Cells; lidé; quercetin; Glucosides; receptory aromatických uhlovodíků; Quercetin; Receptors, Aryl Hydrocarbon; buňky Hep G2; rutin; cytochrom P-450 CYP1A1; Cytochrome P-450 CYP1A1; glukosidy; Humans